A short review on polyaniline (PANI) based nanocomposites for various applications: enhancing the electrical conductivity - Nor Aisah, Khalid; Jeefferie, Abd Razak; Hazman, Hasib; Mohd Muzafar, Ismail; Noraiham, Mohamad; Ramli, Junid; Poppy, Puspitasari (IOP Publishing, 2020)
This short review has summarized the significance of polyaniline (PANI) advanced polymer that focusing into their modification strategy, electrical conductivity and various potential applications. PANI is one type of conductive polymer that was synthesized by oxidative aniline polymerization with varied concentration of acid dopant. In recent year, many researches has been conducted specifically to enhance the electrical conductivity of PANI. There have been numbers of studies involving PANI that specially reported the electrical conductivity could be improved through proper dopant (acid) selection and robust composite strategy. The PANI based nanocomposite shows higher electrical conductivity by integrating it with nanofiller due to the filler-matrix interface contact. Therefore, by modifying the PANI properties, it could be benefited for various potential application in the future.